Population policies, fertility, women's human capital, and child quality - T. Paul Schultz (Institute for the Study of Labor (IZA), 2007)
Population policies are defined here as voluntary programs which help people control their fertility and expect to improve their lives. There are few studies of the long-run effects of policy-induced changes in fertility on the welfare of women, such as policies that subsidize the diffusion and use of best practice birth control technologies. Evaluation of the consequences of such family planning programs almost never assess their long-run consequences, such as on labor supply, savings, or investment in the human capital of children, although they occasionally estimate the short-run association with the adoption of contraception or age-specific fertility. The dearth of long-run family planning experiments has led economists to consider instrumental variables as a substitute for policy interventions which not only determine variation in fertility but are arguably independent of the reproductive preferences of parents or unobserved constraints that might influence family life cycle behaviors. Using these instrumental variables to estimate the effect of this exogenous variation in fertility on family outcomes, economists discover these cross effects of fertility on family welfare outcomes tend to be substantially smaller in absolute magnitude than the OLS estimates of partial correlations referred to in the literature as evidence of the beneficial social externalities associated with the policies that reduce fertility. The paper summarizes critically the empirical literature on fertility and development and proposes an agenda for research on the topic.
urn:nbn:de:101:1-20080401153
Keywords: 330; Familienplanung; Wirkungsanalyse; Fruchtbarkeit; Familie; Lebensstandard; Frauen; Zeitallokation; Frauenbildung; Wohlfahrtseffekt; Entwicklungsländer